Wizerunek teściowej we współczesnej prasie kobiecej - Sapia-Drewniak, Eleonora (Karkonoska Państwowa Szkoła Wyższa, 2011)
The present-day media and women's magazines in particular, offer articles on different aspects of mother-in-law and daughter-in-law relationship. They present the relationship problems that arise between the mother, her married son and her daughter-in-law as well as the mother-in-law's unacceptable behaviour, her taking part in running the household and participation in bringing up the grandchildren. The magazines also include advice, both for the mother-in-law and the daughter-in-law, which focuses on the positive aspects of their mutual relations. Analysing the articles on contemporary mothers-in-law, it can be seen that the mother-in-law's image they produce remains in keeping with commonplace stereotypes. The older woman's faults are often exaggerated; her values, beliefs and her chosen style of living are disregarded. A responsibility for the problems young married couples experience isattributed to her. The editors of women's magazines, in an effort to bring about a modification of the stereotype, show how to change and improve daughter-in-law and mother-in-law relationships.
Keywords: women's magazines; mother-in-law; family; women; intrafamilial relationships